2010
DOI: 10.1523/jneurosci.2862-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Directly Modulates 26S Proteasome Activity

Abstract: Parkinson's disease (PD) is a common neurodegenerative disease that involves the deterioration of dopaminergic neurons in the substantia nigra pars compacta. Although the etiology of PD remains poorly understood, recent genetic, postmortem, and experimental evidence shows that abnormal protein accumulation and subsequent aggregate formation are prominent features of both sporadic and familial PD. While proteasome dysfunction is observed in PD, diverse mutations in the parkin gene are linked to early-onset auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 48 publications
3
45
0
Order By: Relevance
“…In contrast, we did not find any general effect of E6AP on proteasomal processivity. Parkin, a RING finger Ub ligase, has also been shown to bind the proteasome and to modulate its activity (91). However, neither UBE3C nor E6AP seemed to affect the proteasome activity itself, since siRNA knockdown of either did not alter the level of the full-length EGFP-Myc protein (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, we did not find any general effect of E6AP on proteasomal processivity. Parkin, a RING finger Ub ligase, has also been shown to bind the proteasome and to modulate its activity (91). However, neither UBE3C nor E6AP seemed to affect the proteasome activity itself, since siRNA knockdown of either did not alter the level of the full-length EGFP-Myc protein (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Several groups have shown that parkin recruitment to the 26 S proteasome via its Ubl domain increases the 26 S proteasomal activity (23,59). Recently Chaugule et al (50) found that the parkin Ubl domain inhibits its self-ubiquitination by binding to the intrinsic RING1 IBR and RING2 domains, thus keeping parkin in an inhibited state.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of genes involved in heritable forms of PD, including Parkin an E3 ubiquitin ligase (12), have greatly influenced our understanding of the molecular mechanisms underlying neurodegeneration in this disorder (13). Indeed, it has been postulated that parkin mutations impair the UPS of protein degradation, leading to the accumulation of toxic misfolded or aggregated proteins (14,15). More recently, considerable attention has been focused on the role of Parkin in mitochondrial quality control (MQC) (16)(17)(18).…”
mentioning
confidence: 99%